2008
DOI: 10.1177/0278364908095118
|View full text |Cite
|
Sign up to set email alerts
|

Robot Odor Localization: A Taxonomy and Survey

Abstract: Robotic odor localization has become a prominent research area in recent years. It promises many valuable practical applications, and contributes to the knowledge of biological odor localization, which has in many cases been the source of inspiration. There have been a diversity of approaches, implemented in both simulated and practical experiments, with a wide variety of platforms, and in a number of environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
167
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(169 citation statements)
references
References 93 publications
(111 reference statements)
0
167
0
2
Order By: Relevance
“…Ground robots have demonstrated steering, distance estimation, and obstacle avoidance [27][28]. They have also been used for olfactory-related tasks in order to detect, localize, and navigate toward odor cues [29]. Rugged, wheeled robots have been taken out of the lab and utilized outdoors to replicate the path integration and landmark steering of ants [28].…”
Section: B Insect Behavior and Cognitive Embodimentmentioning
confidence: 99%
“…Ground robots have demonstrated steering, distance estimation, and obstacle avoidance [27][28]. They have also been used for olfactory-related tasks in order to detect, localize, and navigate toward odor cues [29]. Rugged, wheeled robots have been taken out of the lab and utilized outdoors to replicate the path integration and landmark steering of ants [28].…”
Section: B Insect Behavior and Cognitive Embodimentmentioning
confidence: 99%
“…A survey of previous research in odor source localization and mapping can be found in [3], where a comprehensive taxonomy is defined and a multitude of solutions are discussed.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work in the field has resulted in a significant number of methods for odor tracking, of which a detailed survey is provided in [14]. Many algorithms take inspiration from living creatures, such as bacteria [4] or silkworm moths [20], and generally operate by switching a single robot among a set of simple behaviors.…”
Section: Introductionmentioning
confidence: 99%